Factors that determine the occurrence of stress in nursing professionals (Research, Society and Development, 2023)
The objective of this study is to understand the determinant factors for the occurrence of Burnout Syndrome in Nursing Professionals. An integrative literature review was carried out and searched in the LILACS, BDENF and SCIELO databases of articles published from January 2015 to December 2022, and the data were systematized using the Content Analysis technique. In total, 14 articles were found that met the inclusion criteria of this study. Thus, it was identified that the main determining factors for the occurrence of Burnout Syndrome among professionals are organizational, individual, work and social. Due to several factors, it can be seen as: constant and periodic exhaustion, the demands of the sectors in which the nursing professional works, the double workload in search of a better salary, social isolation due to fatigue, misunderstandings in the work environment, the lack of tolerance for errors, among other aspects, which causes the nursing professional to enter a state of total stress and, therefore, acquire Burnout syndrome.